Partnering in Principal Preparation Program Redesign - Leggett, Stacy; Desander, Marguerita; Evans, Sam (Educational (Re)naissance, 2022)
Research findings have identified the importance of university/district partnerships in the preparation of principals along with points of dissatisfaction of traditional preparation programs outcomes. While change had and was occurring in some programs, impactful change in the quality of programs and program completers must involve all stakeholders including partnering districts and state agencies in the redesign of preparation programs. This paper examines the local and state context as foundational to the redesign process and the engagement of one university’s use of Wallace Foundation funds to engage area school districts and the state Professional Standards Board in the re-envisioning of its principal preparation program.